2017
DOI: 10.1039/c7tc00868f
|View full text |Cite
|
Sign up to set email alerts
|

Oligo(maleic anhydride)s: a platform for unveiling the mechanism of clusteroluminescence of non-aromatic polymers

Abstract: The mechanism of clusteroluminescence has been unveiled by investigating maleic anhydride-based polymers and copolymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
149
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(153 citation statements)
references
References 41 publications
2
149
0
2
Order By: Relevance
“…Nonconventional fluorescent biogenic and synthetic polymers without aromatic structures have recently attracted considerable attention, and their clusteroluminescence mechanism behind this abnormal phenomenon is increasingly deciphered . For instance, Tang and co‐workers found that the intra‐ and inter‐chain n →π* interaction of carbonyl groups plays a crucial role during the emission for oligo(maleic anhydride)s (OMAhs) in the aggregated state/condensed phase . Zhang and co‐workers also proposed clustering‐triggered emission mechanism, namely the clustering of nonconventional chromophores and subsequent electron cloud can overlap with the simultaneous rigidification of conformation in the process of poly(amino acids).…”
Section: Methodsmentioning
confidence: 99%
“…Nonconventional fluorescent biogenic and synthetic polymers without aromatic structures have recently attracted considerable attention, and their clusteroluminescence mechanism behind this abnormal phenomenon is increasingly deciphered . For instance, Tang and co‐workers found that the intra‐ and inter‐chain n →π* interaction of carbonyl groups plays a crucial role during the emission for oligo(maleic anhydride)s (OMAhs) in the aggregated state/condensed phase . Zhang and co‐workers also proposed clustering‐triggered emission mechanism, namely the clustering of nonconventional chromophores and subsequent electron cloud can overlap with the simultaneous rigidification of conformation in the process of poly(amino acids).…”
Section: Methodsmentioning
confidence: 99%
“…The origin of fluorescence in those aliphatic polymers have been explained by clusteroluminescence, considering the roles of several structural aspects, such as location of tertiary aliphatic‐amines in branching units of hyperbranched polymers,2f oxygen‐amine like “contact” donor–acceptor complexes,2f hydrogen bond,2j coordination bond‐assisted aggregation, and interpenetration of lone pair ( n ) of one carbonyl group of amide in empty π* orbital of another adjacent carbonyl group of amide/ester,2i,k in decreasing the interior mobility of rigid structures. However, the precise detection of fluorophores and associated mechanisms of fluorescence based on simultaneous roles of hydrogen bonding, structural rigidity, and clusteroluminescence, have not been reported to date.…”
Section: Methodsmentioning
confidence: 99%
“…To achieve solid-state room-temperature phosphorescence,t he choice of functional groups,i ntermolecular interactions,and p-p interactions become very important. [21] In such cases,a saconsequence of the high band gap of the molecular entities,the effective band gap of the bulk materials often appears near the blue edge of the visible spectrum. Br) can increase the extent of intersystem crossing, weak interactions such as hydrogen bonding and halogen bonding can lock molecules in the condensed state,thereby enhancing the chances of observing phosphorescence.…”
Section: Luminogens In the Solid Statementioning
confidence: 99%